Leverage of mHealth integration in Maternal and child health services and during COVID-19 - Jabeen , Rawshan; Mohammad , Ameer (Journal of the Pakistan Medical Association, 2023)
The growing use of mobile phones has enabled potential mobile health users to respond to various healthcare crises, even during the Covid-19 pandemic. In low- and middle-income countries where people lack access to basic healthcare, various "mHealth" interventions have been proven. Several “mHealth” interventions have been proven, especially in low- and middle-income countries where people don’t have access to basic healthcare services. In addition, it would facilitate public health researchers in developing new ways to improve the sustainability of MNCH programmes during emergencies or public health alerts. Furthermore, it would help public health researchers in developing new ways for sustainable MNCH programmes that continue to function during any emergency or public health alert circumstances. This article aims to provide evidence of mHealth integration in Pakistan’s MNCH programme and to look into unique techniques used during the Covid-19 pandemic. —Continue